2015
DOI: 10.1111/omi.12143
|View full text |Cite
|
Sign up to set email alerts
|

Secreted adenosine triphosphate from Aggregatibacter actinomycetemcomitans triggers chemokine response

Abstract: Extracellular ATP (eATP) is an important intercellular signaling molecule secreted by activated immune cells or released by damaged cells. In mammalian cells, a rapid increase of ATP concentration in the extracellular space sends a danger signal, which alerts the immune system of an impending danger, resulting in recruitment and priming of phagocytes. Recent studies show that bacteria also release ATP into the extracellular milieu, suggesting a potential role for eATP in host-microbe interactions. It is curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…It has also been shown that eATP promotes biofilm formation in periodontal disease as well as detachment of bacteria from Fusobacterium nucleatum biofilm into its planktonic form to build new colonies [91,92]. Extracellular ATP is also involved in maintaining inflammation and bone resorption in periodontal disease via: (1) P2X7 mediated cytokine release by immune cells and subsequent osteoclast activation [93], (2) direct P2X7 mediated fibroblast activation and chemokine production (IL-8, CXCL-1, CXCL-2, and MCP-1) on the mRNA as well as the protein level, and (3) its chemotactic properties as an attractant for leukocytes [94].…”
Section: Extracellular Atp As An Inter-kingdom Signaling Moleculementioning
confidence: 99%
“…It has also been shown that eATP promotes biofilm formation in periodontal disease as well as detachment of bacteria from Fusobacterium nucleatum biofilm into its planktonic form to build new colonies [91,92]. Extracellular ATP is also involved in maintaining inflammation and bone resorption in periodontal disease via: (1) P2X7 mediated cytokine release by immune cells and subsequent osteoclast activation [93], (2) direct P2X7 mediated fibroblast activation and chemokine production (IL-8, CXCL-1, CXCL-2, and MCP-1) on the mRNA as well as the protein level, and (3) its chemotactic properties as an attractant for leukocytes [94].…”
Section: Extracellular Atp As An Inter-kingdom Signaling Moleculementioning
confidence: 99%
“…The sequential activation of and crosstalk between microglia and astrocytes is now known to be performed by soluble mediators, such as adenosine, growth factors, inflammatory chemokines and cytokines [3,8,9]. Among these mediators, chemokines are 8-14-kDa secreted proteins with conserved cysteine residues in their sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the transposon inserts was determined in 31 randomly picked transconjugants by determining their ability to grow on kanamycin resistant agar after seven passages. At the 7th passage, bacterial cells would have undergone at least 150 generations since the doubling time of A. actinomycetemcomitans is about 3 h ( Ding et al, 2016 ). This is consistent with previous reports that transposon insertions are stably inherited in A. actinomycetemcomitans ( Kolodrubetz and Kraig, 1994 ; Thomson et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%